Towards the Adoption of Construction 4.0 Technology: Exploring the Role of Organizational Citizenship Behavior - Wee , Wan Li; Jaafar, Mastura (Research in Management of Technology and Business, 2024)
Organizational Citizenship Behavior (OCB) is an individual’s contribution to exceeding the demands of the role in the workplace. The construction industry is on the brink of a paradigm shift with the emergence of Construction 4.0 (C4.0) technologies. A strategic roadmap outlined in the Construction 4.0 Strategic Plan (2021-2025) identifies twelve pivotal technologies poised to revolutionize construction processes. However, the acceptance and deployment of C4.0 technologies among industry players have not been encouraging. This research explores how OCB could influence the adoption of C4.0 technologies in the construction industry. Within this context, the Technology Acceptance Model (TAM) provides a theoretical lens to elucidate user acceptance dynamics. Based on the Social Exchange Theory, this study examines the relationship between the five dimensions of OCB: altruism, conscientiousness, sportsmanship, civic virtue, and courtesy, with the technology acceptance measures, which consist of perceived usefulness (PU) and perceived ease of use (PEOU). The objectives of this paper are to 1) identify key OCB indicators relevant to C4.0 adoption and 2) identify the relationship between OCB and C4.0. Data will be collected from Grade 7 contractors in Malaysia through quantitative methods to validate the hypothesized relationships. Civic virtue, courtesy and conscientiouosness were the top 3 key ocb indicator relevant to C4.0 adoption. Altruism shows significant relationship with PU, meanwhile civic virtue show signficant relatioship with PEOU. The results demonstrate that Civic Virtue, Courtesy, and Conscientiousness emerge as the top three key OCB indicators critical to adopting Construction 4.0 technology. Notably, Altruism shows a significant positive relationship with the technology’s PU, while Civic Virtue is strongly associated with PEOU. These findings underscore the importance of specific OCB behaviors in facilitating the effective integration of C4.0 within organizations. Ultimately, this research endeavours to fill a crucial gap in the literature by elucidating the role of OCB in influencing attitudes and behaviours toward C4.0 technology adoption in the construction industry.